Entirely different stories: autoethnography as women's literacy practice in southern Africa - Johnson, Stacey J., author; Jacobi, Tobi, advisor; Doe, Sue, committee member; Pearson, Jonna, committee member (Colorado State University. Libraries, 2011)
This thesis suggests autoethnography as one methodology for more democratic adult literacy instruction in rural Southern Africa. Because of my experiences working as a Rural Education Development volunteer in Zambia, I am concerned with the postcolonial implications of many of the educational initiatives employed in the region. Using a postcolonial feminist framework, I seek to situate autoethnography as one way to both resist what Chimamanda calls the "one story of Africa" and to sponsor dual language literacy acquisition in rural Zambia. In this thesis, I work to analyze the mission statements of existing educational projects as representative of the limited narratives written for people in rural communities. I also propose a collaborative autoethnographic writing project based on existing community writing projects/theory that locate literacy as a site of resistance and hybridity, encouraging story-telling by and with others rather than about Others.
Keywords: autoethnography; community writing; feminism; Freire; postcolonial literatures; Zambia